2010
DOI: 10.1016/j.neuroscience.2010.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis for improgan antinociception

Abstract: Improgan, the prototype compound of a novel class of non-opioid analgesic drugs derived from histamine antagonists, attenuates thermal and mechanical nociception in rodents following intracerebroventricular administration. Improgan does not bind to known opioid, histamine or cannabinoid receptors, and its molecular target has not been identified. It is known however that improgan acts directly in the periaqueductal gray and the rostral ventromedial medulla to produce its antinociceptive effects, and that inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…The holding temperature obviates any concern that apparent effects on reflex latency could be attributed to changes in skin temperature. Previous work has shown that response latencies and neuronal response properties are stable for a period of several hours with this testing protocol (Edelmayer et al 2009;Heinricher et al 2004Heinricher et al , 2010Kincaid et al 2006;Martenson et al 2009). …”
Section: E T H O D Smentioning
confidence: 89%
See 4 more Smart Citations
“…The holding temperature obviates any concern that apparent effects on reflex latency could be attributed to changes in skin temperature. Previous work has shown that response latencies and neuronal response properties are stable for a period of several hours with this testing protocol (Edelmayer et al 2009;Heinricher et al 2004Heinricher et al , 2010Kincaid et al 2006;Martenson et al 2009). …”
Section: E T H O D Smentioning
confidence: 89%
“…NEUTRAL-cells do not respond to improgan (Heinricher et al 2010) and remained unresponsive following CC12 pretreatment (n ϭ 5; data not shown).…”
Section: Effects Of Cc12 On Behavioral and Neuronal Responses To Imprmentioning
confidence: 96%
See 3 more Smart Citations